From Bethlehem to the Classroom: An Incarnational Paradigm for Christian Early Childhood Education - Gunawan; Sri Pertiwi (Real Kiddos: Jurnal Pendidikan Anak Usia Dini, 2026)
This article develops an incarnational pedagogical paradigm for Christian early childhood education, grounded in the biblical narrative of the Incarnation as presented in Luke 2:1-20 and John 1:14. Employing a constructive theological method, the study integrates exegetical analysis of the selected biblical texts with contemporary educational theory and developmental psychology to formulate a holistic framework for children aged 0-6. Four interconnected dimensions are proposed: pedagogy as hospitality, curriculum as narrative participation, assessment as gift and growth, and community as the primary site of formation. The study argues that the Incarnation, understood as God's embodied presence in Jesus Christ, fundamentally reorders the logic of Christian education by displacing cognitive-centered and performance-driven models in favor of a framework centered on embodiment, relational presence, and prevenient grace. Children are affirmed as imago Dei, possessing intrinsic dignity and spiritual capacity prior to any academic achievement. The study concludes that when incarnational theology fully inhabits educational practice, the Christian classroom becomes a modern Bethlehem, a sacred space where divine love is made concretely real in the lives of young children and where the church reclaims its formative role in holistic child development. Keywords: incarnational theology; Christian early childhood education; embodied pedagogy; imago Dei; spiritual formation Abstrak Artikel ini mengembangkan paradigma pedagogis inkarnasional untuk pendidikan anak usia dini Kristen, yang berlandaskan pada narasi Alkitab tentang Inkarnasi sebagaimana tertuang dalam Lukas 2:1-20 dan Yohanes 1:14. Dengan menggunakan metode teologi konstruktif, penelitian ini mengintegrasikan analisis eksegesis teks Alkitab yang dipilih dengan teori pendidikan kontemporer dan psikologi perkembangan untuk merumuskan kerangka holistik bagi anak usia 0-6 tahun. Empat dimensi yang saling terhubung diusulkan, yakni pedagogi sebagai keramahtamahan, kurikulum sebagai partisipasi naratif, penilaian sebagai anugerah dan pertumbuhan, serta komunitas sebagai ruang pembentukan utama. Penelitian ini berargumen bahwa Inkarnasi, yang dipahami sebagai kehadiran Allah yang menjelma dalam diri Yesus Kristus, secara fundamental menyusun ulang logika pendidikan Kristen dengan menggeser model yang berpusat pada kognisi dan berorientasi kinerja, menuju kerangka yang berpusat pada penjelmaan, kehadiran relasional, dan anugerah yang mendahului. Anak-anak diteguhkan sebagai imago Dei, yang memiliki martabat intrinsik dan kapasitas spiritual sebelum pencapaian akademis apa pun. Penelitian ini menyimpulkan bahwa ketika teologi inkarnasional sepenuhnya menghuni praktik pendidikan, ruang kelas Kristen menjadi Betlehem modern, yakni ruang sakral di mana kasih ilahi diwujudkan secara nyata dalam kehidupan anak-anak usia dini, dan di mana gereja kembali mengemban perannya dalam pengembangan anak secara holistik. Kata Kunci: teologi inkarnasional; pendidikan anak usia dini Kristen; pedagogi terwujud; imago Dei; pembentukan spiritual